Ranking of crop plants according to their potential to uptake and accumulate contaminants of emerging concern - Christou, Anastasis; Papadavid, George; Dalias, Panagiotis; Fotopoulos, Vasileios; Michael, Costas; Maria Bayona, Josep; Piña, Benjamin; Fatta-Kassinos, Despo (My University, 2019)
The reuse of treated wastewater (TWW) for irrigation and the use of biosolids and manures as soil amendment constitute significant pathways for the introduction of the contaminants of emerging concern (CECs) to the agricultural environment. Consequently, CECs are routinely detected in TWW-irrigated agricultural soils and runoff from such sites, in biosolids- and manure-amended soils, and in surface and groundwater systems and sediments receiving TWW. Crop plants grown in such contaminated agricultural environments have been found to uptake and accumulate CECs in their tissues, constituting possible vectors of introducing CECs into the food chain; an issue that is presently considered of high priority, thus needing intensive investigation. This review paper aims at highlighting the responsible mechanisms for the uptake of CECs by plants and the ability of each crop plant species to uptake and accumulate CECs in its edible tissues, thus providing tools for mitigating the introduction of these contaminants into the food chain. Both biotic (e.g. plants' genotype and physiological state, soil fauna) and abiotic factors (e.g. soil pore water chemistry, physico-chemical properties of CECs, environmental perturbations) have been proven to influence the ability of crop plants to uptake and accumulate CECs. According to authors' estimates, based on the thorough elaboration of knowledge produced by existing relevant studies, the ability of crop plants to uptake and accumulate CECs decrease in the order of leafy vegetables > root vegetables > cereals and fodder crops > fruit vegetables; though, the uptake of CECs by important crop plants, such as fruit trees, is not yet evaluated. Overall, further studies must be performed to estimate the potential of crop plants to uptake and accumulate CECs in their edible tissues, and to characterize the risk for human health represented by their presence in human and livestock food products.
Keywords: Bioaccumulation; Crop evapotranspiration; Leafy vegetable; Plant physiology; Treated wastewater